PENDIDIKAN SENI TEATER; SEKOLAH, TEATER DAN PENDIDIKNYA - Prusdianto Prusdianto (Universitas Negeri makassar, 2018)
Schools that offer theater arts subjects to serve as subjects of art, will provide an opportunity for students to get in touch with the community. Students do not just feel has nothing to do with schools, communities, and nations, but to feel by themselves as a part of civilization. The development of the students is in a social engagement (sense of community, a sense of participation, sense of belonging, a sense of humanity). School as a system includes several components, where each component consists of several factors. With one another interconnected to form a system. Component - a component of the school system consists of inputs (input), process (process), direct output (output) and indirect output (outcome). Theater arts in art class culture is a form of appreciation for the presentation of performances and educational tools. Besides the theater is also a means to shape; (A) student understanding of self and others, (b) the power of interpretation of self, (c) confidence in himself, and (d) awareness in collaboration with a large group consisting of persons in carrying out the production of a show. An educator who has understood the intent and purpose of teaching is expected to carry it out easily. Be a challenge, that here also demanded creativity teachers to make the bait-new, fresh, and not boring for the child, and thus, will be obtained fresh feedback and original anyway.